Effects of future climate change and habitat loss in the distribution of frog species in the Ecuadorian Andes - Barragán Altamirano, Dayana Gabriela (2015)
The biodiversity of the tropical Andes is threatened by climate change and habitat loss. Many studies have focused in the future effects of climate change on species distribution and conservation but few have included the effects habitat loss in their predictive studies. In this study we evaluated the combined effects of these two threats in the future distributions of endemic frogs species of the Ecuadorian Andes to the year 2050. We used ecological niche models to predict the distribution of 68 frog species using a combination of four Representative Concentration Pathway scenarios of future climate and four scenarios of dispersal capabilities. We constructed a predictive model of natural vegetation loss in Ecuador by 2050 using the Multi-Layer Perceptron neural network and Markov Chain analysis algorithms. We also explored how changes in frogs species richness resulting from climate change and habitat loss correlate with altitude and magnitude of climate change. Our results show climate change had a positive effect on the future distribution area of ~60% of the frogs species, and a negative effect in ~40%. Dispersal capabilities greatly influenced the effect of climate change and habitat loss on distribution areas. Change in species richness due to climate change show positive correlations mainly with altitude, temperature and precipitation. Future habitat loss will exacerbate the negative effects of climate change and will limit its positive effects on frogs species’ distributions. Our results suggest that, under a limited dispersal scenario, most Andean frogs species will be unable to effectively colonize new suitable habitat as result of habitat loss. Conversely, under dispersal scenarios of 5 km per year or more, climate change could have a positive effect in the area of distribution of most species. There are no specific studies on the dispersal capabilities of Andean frogs. Our study, illustrates the role of dispersal in the future effects of climate change and habitat loss.